2021
DOI: 10.1080/10640266.2021.1985807
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic stress, body shame, and internalized weight stigma as mediators of change in disordered eating: a single-arm pilot study of the Body Trust® framework

Abstract: To enhance access to evidence-based treatment it is increasingly important to evaluate scalable virtual programs that support the needs of those struggling with disordered eating. This study described a scientifically grounded, trauma-informed framework known as Body Trust,® and aimed to pilot test the preliminary effectiveness and mechanisms of change in a Body Trust® program to improve disordered eating. Using quality outcomes data, we examined 70 mostly white (87%) femaleidentifying (97%) individuals enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 123 publications
(141 reference statements)
0
12
0
Order By: Relevance
“…Participant age showed promise as a factor predictive of drop‐out , with nine out of 21 studies ( n = 70–680; 19 RCTs) finding younger age to predict a higher likelihood of drop‐out (Beintner, Emmerich, et al, 2019; Flatt et al, 2022; Linardon, Broadbent, et al, 2022; Linardon, Messer, et al, 2022; Linardon, Messer, Shatte, et al, 2021; Linardon, Shatte, et al, 2022; Linardon, Shatte, Rosato, & Fuller‐Tyszkiewicz, 2020; Mensinger, 2021; Rohde et al, 2017). In studies finding a significant association, samples mostly consisted of female participants who were highly symptomatic or were at risk of disordered eating.…”
Section: Resultsmentioning
confidence: 99%
“…Participant age showed promise as a factor predictive of drop‐out , with nine out of 21 studies ( n = 70–680; 19 RCTs) finding younger age to predict a higher likelihood of drop‐out (Beintner, Emmerich, et al, 2019; Flatt et al, 2022; Linardon, Broadbent, et al, 2022; Linardon, Messer, et al, 2022; Linardon, Messer, Shatte, et al, 2021; Linardon, Shatte, et al, 2022; Linardon, Shatte, Rosato, & Fuller‐Tyszkiewicz, 2020; Mensinger, 2021; Rohde et al, 2017). In studies finding a significant association, samples mostly consisted of female participants who were highly symptomatic or were at risk of disordered eating.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies measured history of traumatic events, with eight of these specifically assessing childhood trauma history. Four studies assessed PTSD diagnosis and one study by Mensinger (2021) measured traumatic stress as another indicator of trauma-related symptoms but did so using a common self-report PTSD diagnostic tool. The results of the articles are reported below, organized by treatment outcome, and distinguished between trauma exposure and trauma-related symptoms (including PTSD).…”
Section: Resultsmentioning
confidence: 99%
“…Of the four studies that investigated the impact of PTSD diagnosis or symptoms on eating disorder pathology, three found significant effects ( Hazzard et al, 2021 ; Mensinger, 2021 ; Scharff et al, 2021 ) and one found no effect on eating disorder outcomes ( Mitchell et al, 2021 ). Two studies with significant findings measured PTSD diagnosis and found that it was associated with more frequent binge eating at discharge when controlling for baseline binge eating ( Hazzard et al, 2021 ) and predicted greater symptom recurrence from discharge to a 6-month follow-up ( Scharff et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these interventions, it is important to note that most target challenging fatphobia in health care students, providers, and educators rather than addressing internalized weight stigma among those who have lived experience of higher weight. There are several recent promising interventions, however, that target internalized weight stigma in large-bodied individuals with disordered eating (Brownstone et al, 2021; Dunaev et al, 2018; Mensinger, 2022). To further enhance these emerging interventions, clinicians must understand how large-bodied clients make sense of and heal from their experiences with weight stigma to support the development of these interventions for large-bodied individuals.…”
Section: Weight Stigma Psychological Distress and Disordered Eatingmentioning
confidence: 99%
“…Relatedly, evidence suggests that weight stigma is associated with increased restrained, emotional, and uncontrolled eating (Lin et al, 2020) and that youth with disordered eating experience greater weight bias (Najjar et al, 2018). Internalized weight stigma has also been found to mediate treatment outcomes for those with disordered eating (Mensinger, 2022). Such research suggests that weight stigma may be a particularly important intervention point for those with disordered eating.…”
Section: Weight Stigma Psychological Distress and Disordered Eatingmentioning
confidence: 99%